A new analytical method for the simultaneous quantification of isoflavones and lignans in 25 green coffee samples by HPLC-MS/MS. (30th September 2020) - Angeloni, Simone; Navarini, Luciano; Khamitova, Gulzhan; Maggi, Filippo; Sagratini, Gianni; Vittori, Sauro; Caprioli, Giovanni
Graphical abstract: Highlights: A new analytical method for lignan and isoflavone quantitation has been developed. Base hydrolysis followed by enzymatic digestion was the best extraction process. Lignans occurred in higher concentrations than isoflavones. Matairesinol was not present in any samples. Ethiopian green coffees may be a good source of lignans. Abstract: Green coffee, the raw material of roasted coffee and coffee beverages, is one of the most widely traded commodities worldwide. There is a dearth of studies on its content in phytoestrogens such as isoflavones and lignans. Previously, we developed an efficient method for the simultaneous quantification of 6 isoflavones (daidzin, genistin, daidzein, genistein, formononetin and biochanin A) and 3 lignans (secoisolariciresinol, matairesinol and lariciresinol) in green coffee by using HPLC-MS/MS. Several extraction processes were evaluated and the best performing, base hydrolysis followed by enzymatic digestion, was validated and used to analyse 25 different coffee samples, 1 Coffea canephora and 24 Coffea arabica, from different countries. Lignans (total content: 286.5–8131.8 µg kg −1 ) were found in higher concentration than isoflavones (total content: 3.4–300.0 µg kg −1 ) and the most abundant were secoisolariciresinol (172.6–5714.1 µg kg −1 ) and lariciresinol (113.9–2417.7 µg kg −1 ). Notably, the Ethiopian coffee samples contained the highest levels of these compounds.